Hemolysis of human erythrocytes induced by tamoxifen is related to disruption of membrane structure - Cruz Silva, M. M. (2000)
Tamoxifen (TAM), the antiestrogenic drug most widely prescribed in the chemotherapy of breast cancer, induces changes in normal discoid shape of erythrocytes and hemolytic anemia. This work evaluates the effects of TAM on isolated human erythrocytes, attempting to identify the underlying mechanisms on TAM-induced hemolytic anemia and the involvement of biomembranes in its cytostatic action mechanisms. TAM induces hemolysis of erythrocytes as a function of concentration. The extension of hemolysis is variable with erythrocyte samples, but 12.5 [mu]M TAM induces total hemolysis of all tested suspensions. Despite inducing extensive erythrocyte lysis, TAM does not shift the osmotic fragility curves of erythrocytes. The hemolytic effect of TAM is prevented by low concentrations of [alpha]-tocopherol ([alpha]-T) and [alpha]-tocopherol acetate ([alpha]-TAc) (inactivated functional hydroxyl) indicating that TAM-induced hemolysis is not related to oxidative membrane damage. This was further evidenced by absence of oxygen consumption and hemoglobin oxidation both determined in parallel with TAM-induced hemolysis. Furthermore, it was observed that TAM inhibits the peroxidation of human erythrocytes induced by AAPH, thus ruling out TAM-induced cell oxidative stress. Hemolysis caused by TAM was not preceded by the leakage of K+ from the cells, also excluding a colloid-osmotic type mechanism of hemolysis, according to the effects on osmotic fragility curves. However, TAM induces release of peripheral proteins of membrane-cytoskeleton and cytosol proteins essentially bound to band 3. Either [alpha]-T or [alpha]-TAc increases membrane packing and prevents TAM partition into model membranes. These effects suggest that the protection from hemolysis by tocopherols is related to a decreased TAM incorporation in condensed membranes and the structural damage of the erythrocyte membrane is consequently avoided. Therefore, TAM-induced hemolysis results from a structural perturbation of red cell membrane, leading to changes in the framework of the erythrocyte membrane and its cytoskeleton caused by its high partition in the membrane. These defects explain the abnormal erythrocyte shape and decreased mechanical stability promoted by TAM, resulting in hemolytic anemia. Additionally, since membrane leakage is a final stage of cytotoxicity, the disruption of the structural characteristics of biomembranes by TAM may contribute to the multiple mechanisms of its anticancer action.